Staphylococcus epidermidis SAS1: new probiotic candidate for obesity and allergy treatment their mechanistic insights and cytotoxicity evaluation - Sharma, Sonia; Sharma, Aarjoo; Sodhi, Gurleen Kaur; George, Nancy; Alarjani, Khaloud Mohammed; Mukherjee, Arkadeep; Kumar Rath, Santosh; Kaur, Ramandeep; Dwibedi, Vagish (Frontiers in Microbiology, 2025)
BackgroundProbiotics are live bacteria that provides numerous healthy and beneficial effects to the consumers. The present study aimed to investigate the effect of a probiotic candidate Staphylococcus epidermidis SAS1, in immunoregulation and obesity management.Methods: This probiotic candidate was isolated from a soil sample collected from a region of fruit waste decomposition. In vitro cytotoxicity was assessed using the THP-1 (human leukemia monocytic cell line) cells using MTT assay.ResultsAn IC50 value of 47.52 ± 0.18 μg/mL and cell shrinkage were observed along with the release of cellular content of THP-1 cells. The higher production of reactive oxygen species and lesser release of interleukins (IL-4, 5, and 13) are attributed to the antiallergic potential of this strain. Furthermore, in vitro cytotoxicity evaluation using 3T3-L1 cells identified this strain as a promising candidate for anti-obesity treatment. The observed IC50 value was 514.4 ± 0.061 μg/mL.DiscussionThis extract was shown to have good lipase-inhibiting enzyme activity and was reported to prevent adipogenesis, depicted by increased HDL levels and decreased LDL and triglyceride levels. These results suggested that Staphylococcus epidermidis SAS1 may have therapeutic use in the treatment of obesity and allergies.